Patch
A patch with a high-moisture-permeable support layer and DMSO-containing adhesive layer addresses adhesiveness issues, ensuring prolonged adhesion and effective drug delivery.
Patent Information
- Application Number
- JP2024192773
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2016-12-28
- Filing Date
- 2024-11-01
- Publication Date
- 2025-01-20
- Estimated Expiration
- 2037-12-26
AI Technical Summary
The adhesiveness of patches containing dimethyl sulfoxide (DMSO) decreases over time, leading to potential peeling before the completion of treatment due to plasticization of the adhesive layer.
A patch design incorporating a support layer with high moisture permeability and an adhesive layer containing DMSO, adhesive, and optionally a drug, which maintains adhesiveness by allowing DMSO evaporation, thereby preventing peeling.
The patch maintains sufficient adhesion for extended periods, ensuring reliable drug delivery and achieving maximum plasma concentration of analgesic and anti-inflammatory drugs like ketoprofen, diclofenac sodium, or indomethacin.
Smart Images

Figure 2025010375000004 
Figure 2025010375000005 
Figure 2025010375000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a patch. [Background technology]
[0002] Dimethyl sulfoxide (DMSO) is used in formulations to dissolve drugs. For example, Patent Document 1 discloses a patch of diclofenac sodium that uses DMSO as a dissolving agent. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] International Publication No. 2013 / 191128 Summary of the Invention [Problem to be solved by the invention]
[0004] In general, the adhesiveness of a patch gradually decreases with time. The present inventors have found that when DMSO is incorporated into the adhesive layer of a patch, the composition that gives the patch adhesiveness is plasticized, and the adhesiveness of the adhesive layer decreases. The present inventors have also found that when a patch containing DMSO is applied for a long period of time (e.g., 24 hours), sufficient adhesiveness does not last until the end, and the patch may peel off before the completion of treatment. [Means for solving the problem]
[0005] The present inventors discovered that by combining a DMSO-containing adhesive layer with a support having a specific moisture permeability, the adhesion of the patch after long-term application is significantly improved, and thus completed the present invention.
[0006] The patch of the present invention comprises a support layer and an adhesive layer laminated on the support layer, and the moisture permeability of the support layer is 400 g / m 224 hours or more, and the adhesive layer contains a drug, DMSO, and an adhesive. The moisture permeability of the support layer is 750 g / m 2 - 24 hours or more, 2000g / m 2 May be more than 24 hours.
[0007] The pressure-sensitive adhesive layer may include at least one pressure-sensitive adhesive selected from a rubber-based pressure-sensitive adhesive, an acrylic pressure-sensitive adhesive, and a silicone-based pressure-sensitive adhesive, and may include a styrene-isoprene-styrene block copolymer.
[0008] The drug may be one or more drugs selected from the group consisting of ketoprofen, diclofenac sodium, and indomethacin. The adhesive layer may also contain an organic acid. Effect of the Invention
[0009] According to the patch of the present invention, by using a support layer having high moisture permeability, sufficient adhesion is maintained for a long time. Therefore, even if applied for a long time (for example, 24 hours), the patch is not easily peeled off. As a result, when the drug is a drug having analgesic and anti-inflammatory action, such as ketoprofen, diclofenac sodium or indomethacin, a sufficient cumulative skin permeation amount is more reliably obtained when the patch is applied to the skin of a patient for 24 hours. In addition, the maximum plasma concentration Cmax of the drug is more reliably achieved. Therefore, the patch of the present invention enables more effective drug treatment. [Brief description of the drawings]
[0010] [Figure 1] 1 is a graph showing the relationship between the moisture permeability of a backing layer and the rate of decrease in the mass % concentration of DMSO relative to the total mass of a pressure-sensitive adhesive layer (hereinafter referred to as "DMSO concentration") (Test Example 1). [Diagram 2] 1 is a graph showing the relationship between the moisture permeability of the backing layer and the half-life of the mass % concentration of DMSO relative to the total mass of the pressure-sensitive adhesive layer (Test Example 1). DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] The patch of the present invention comprises a support layer and an adhesive layer laminated on the support layer. The adhesive layer is usually laminated on one side of the support layer, and if necessary, a peelable film is laminated on the other side of the adhesive layer.
[0012] First, the adhesive layer will be described. The adhesive layer is the part that is pressed against the skin when the patch is applied, and contains at least a drug, DMSO, and an adhesive.
[0013] The drug is a component soluble in DMSO. The drug may be a drug having analgesic and anti-inflammatory effects such as loxoprofen, felbinac, flurbiprofen, indomethacin, ketoprofen, and diclofenac sodium, or may be an analgesic or narcotic drug such as buprenorphine, fentanyl, and butorphanol, or other drugs such as clonidine, estradiol, tulobuterol, and oxybutynin. The content of the drug is, for example, 1% by mass to 20% by mass or 2% by mass to 10% by mass with respect to the total mass of the adhesive layer.
[0014] DMSO dissolves the drug and improves the skin permeability of the drug, but at the same time, it causes a decrease in the adhesiveness of the adhesive layer. In order to balance these two, the content of DMSO is preferably 1% by mass to 20% by mass, more preferably 1% by mass to 15% by mass, even more preferably 2% by mass to 10% by mass, and particularly preferably 3% by mass to 10% by mass, based on the total mass of the adhesive layer.
[0015] The ratio of drug to DMSO varies depending on the drug, but for example, when the drug contains diclofenac sodium, the ratio of the mass of diclofenac sodium contained in the adhesive layer of the patch immediately before application is preferably 1:0.3 to 1:4, more preferably 1:0.4 to 1:3, even more preferably 1:0.6 to 1:3, and particularly preferably 1:0.72 to 1:3, from the viewpoints of improving the skin permeability of diclofenac sodium and preventing the precipitation of crystals of diclofenac sodium.
[0016] The adhesive may include at least one adhesive selected from rubber-based adhesives, acrylic-based adhesives, and silicone-based adhesives. Examples of rubber-based adhesives include polyisoprene, polyisobutylene (PIB), polybutadiene, styrene-butadiene-styrene block copolymers, styrene-isoprene-styrene (SIS) block copolymers, styrene-butadiene rubber, styrene-isoprene rubber, and combinations thereof. Among these, SIS block copolymers, PIB, and combinations thereof are preferred from the viewpoint of increasing the skin permeability of drugs and further increasing the adhesiveness of patches, and a mixture of SIS block copolymers and PIB is more preferred. Examples of acrylic adhesives include adhesives obtained by polymerizing or copolymerizing at least one of (meth)acrylic monomers such as (meth)acrylic acid, (meth)acrylic acid-2-ethylhexyl, (meth)acrylate, methyl (meth)acrylate, butyl (meth)acrylate, and hydroxyethyl (meth)acrylate. The silicone-based adhesive contains, as a main component, silicone rubber such as polydimethylsiloxane, polymethylvinylsiloxane, and polymethylphenylsiloxane.
[0017] In the case of a rubber-based adhesive, the content of the adhesive may be 10% by mass to 70% by mass, 10% by mass to 40% by mass, 15% by mass to 50% by mass, 15% by mass to 35% by mass, or 30% by mass to 40% by mass, based on the total mass of the adhesive layer, in terms of adhesiveness of the patch. In the case of an acrylic-based adhesive or a silicone-based adhesive, the content of the adhesive may be 50% by mass to 90% by mass, based on the total mass of the adhesive layer.
[0018] The adhesive layer may further contain an organic acid for the purpose of promoting transdermal absorption of the drug, preventing crystallization of the drug over time, etc. Examples of the organic acid include aliphatic monocarboxylic acids (formic acid, acetic acid, propionic acid, butyric acid, isobutyric acid, valeric acid, caproic acid, enanthic acid, caprylic acid, nonanoic acid, capric acid, lauric acid, oleic acid, linoleic acid, linolenic acid, isostearic acid, sorbic acid, pyruvic acid, etc.), aliphatic dicarboxylic acids (oxalic acid, malonic acid, succinic acid, glutaric acid, adipic acid, sebacic acid, maleic acid, fumaric acid, oxaloacetic acid, etc.), and aliphatic tricarboxylic acids (aconitic acid, propanetricarboxylic acid, cyclohexyl 1-hydroxypropyl 1-propanediol ... Examples of the organic acid include aliphatic carboxylic acids such as carboxylic acids, hydroxy acids (glycolic acid, lactic acid, tartronic acid, glyceric acid, hydroxybutyric acid, malic acid, tartaric acid, citric acid, isocitric acid, sugar acid, gluconic acid, glucuronic acid, ascorbic acid, erythorbic acid, etc.), aromatic carboxylic acids (benzoic acid, gallic acid, salicylic acid, acetylsalicylic acid, phthalic acid, etc.), other organic acids (mesylic acid, pesylic acid, etc.), or salts thereof (for example, alkali metal salts such as sodium salts). Among these organic acids, when the drug is diclofenac sodium, citric acid, oleic acid, mesylic acid, or alkali metal salts thereof are particularly preferred in terms of promoting the transdermal absorption of diclofenac sodium and preventing crystals of diclofenac sodium from precipitating over time. By containing these organic acids, a sufficient cumulative skin permeation amount of the drug can be obtained more reliably. These organic acids may be used alone or in combination of two or more. From the viewpoint of improving the skin permeability of the drug and preventing precipitation of drug crystals over time, the content of the organic acid may be 0.01% by mass to 20% by mass, 0.1% by mass to 15% by mass, or 0.2% by mass to 13% by mass, relative to the total mass of the adhesive layer.
[0019] The pressure-sensitive adhesive layer may further contain a tackifier, a plasticizer, or other additives. The tackifier is, for example, an alicyclic saturated hydrocarbon resin, a hydrogenated rosin ester, a terpene resin, or a combination thereof. The content of the tackifier is, for example, 5% by mass to 60% by mass, 10% by mass to 50% by mass, 25% by mass to 45% by mass, or 30% by mass to 35% by mass, based on the total mass of the pressure-sensitive adhesive layer. The plasticizer is, for example, liquid paraffin or liquid polybutene. The content of the plasticizer is, for example, 7% by mass to 70% by mass, 10% by mass to 60% by mass, or 11% by mass to 25% by mass, based on the total mass of the pressure-sensitive adhesive layer.
[0020] The adhesive layer may be a single layer made of one type of composition, or may be a multilayer made of multiple layers of different compositions. The total thickness of the adhesive layer is preferably 10 μm to 1000 μm, more preferably 30 μm to 300 μm, from the viewpoint of properly adhering the patch to the skin.
[0021] The probe tack value of the adhesive layer is preferably 30gF or more, more preferably 40gF or more. The probe tack value of the adhesive layer may be, for example, 43gF or more, 44gF or more, 53gF or more, 61gF or more, 68gF or more, or 71gF or more. The higher the probe tack value, the better the adhesion of the patch. From the viewpoint of reducing irritation to the skin, the probe tack value may be 2000gF or less, 1500gF or less, or 1000gF or less. In this specification, the probe tack value of the adhesive layer is measured in accordance with the probe tack test method of ASTM D2979.
[0022] Next, the support layer will be described. The support layer supports the pressure-sensitive adhesive layer. The moisture permeability of the support layer is 400 g / m 224 hours or more. When a support layer with such high moisture permeability is used, DMSO gradually evaporates from the patch applied to the skin, improving the adhesiveness of the patch and making it less likely to peel off even when applied for a long period of time. Moisture permeability is originally an index of water permeability, but the present inventors have found that a support with high moisture permeability also has high DMSO permeability (volatility). The moisture permeability of the support layer is, for example, 422 g / m 2 ·Over 24 hours, 750g / m 2 ·Over 24 hours, 2000g / m 2 ·Over 24 hours, 2077g / m 2 ·Over 24 hours, 4000g / m 2 ·Over 24 hours, 5500g / m 2 ·Over 24 hours, 5667g / m 2 24 hours or more or 8408g / m 2 - 24 hours or more. The upper limit of the moisture permeability is 20000g / m 2 When the moisture permeability of the backing layer is within this range, DMSO is more likely to volatilize from the adhesive layer, which is more effective in improving the adhesiveness of the patch.
[0023] The moisture permeability of the support layer in the present invention means the moisture permeability at 40° C. as defined in the JIS Z0208:1976 standard (Test method for moisture permeability of moisture-proof packaging material (cup method)).
[0024] The support layer is preferably a monolayer or laminate of fibers in the form of a cloth (woven, nonwoven, or knitted fabric) or a nonporous or porous film (sheet). The material of the support layer is preferably one or more materials selected from polyester (polyethylene terephthalate (PET), polyethylene isophthalate, polypropylene terephthalate, polypropylene isophthalate, polybutylene terephthalate, polyethylene naphthalate, etc.), polyolefin (polymer or copolymer of vinyl monomers such as ethylene, propylene, vinyl acetate, or acrylonitrile), polyamide (nylon or silk, etc.), polyurethane (PU), or cellulose (cotton or linen, etc.). The cloth (woven, nonwoven, or knitted fabric) may be coated with a rubber composition. The rubber composition includes a rubber-based adhesive. The rubber-based adhesive is, for example, polyisoprene, PIB, polybutadiene, styrene-butadiene-styrene block copolymer, SIS block copolymer, styrene-butadiene rubber, styrene-isoprene rubber, or a combination thereof. The rubber composition may contain a tackifier. The tackifier is, for example, an alicyclic saturated hydrocarbon resin, a hydrogenated rosin ester, a terpene resin, or a combination thereof. The rubber composition may further contain additives such as a plasticizer and a filler. The thickness of the support layer is, for example, 0.1 mm to 2 mm. The basis weight of the support layer is, for example, 30 g / m 2 ~200g / m 2 In this specification, the thickness and basis weight of the support layer are measured in accordance with the standard JIS L 1906:2000.
[0025] When the backing layer is cloth-like, the 50% modulus (JIS L 1018:1999) in both the longitudinal direction (material flow direction) and lateral direction (material width direction) of the backing layer is preferably 1 N / 50 mm to 12 N / 50 mm. When the 50% modulus is 12 N / 50 mm or less, the stress that the patch receives due to the expansion and contraction of the skin is smaller, resulting in good adhesion to the skin.
[0026] When the support layer is a film, the material is preferably one having high moisture permeability (high DMSO permeability) such as polyurethane. A film made of polyurethane is preferred from the viewpoint of enhancing the adhesion to the skin and the elasticity of the patch, since it has excellent elasticity.
[0027] The support layer is preferably, for example, a nonwoven fabric or film made of polyurethane, a knitted fabric made of polyethylene terephthalate, a polyester fabric coated with a rubber composition, or a combination thereof. More specifically, the support layer is preferably a laminate of a film made of polyurethane and a nonwoven fabric made of polyurethane fibers, a nonwoven fabric made of PET fibers, or a polyester fabric coated with a rubber composition.
[0028] In order to prevent the drug from precipitating in an unused patch, the DMSO concentration in the patch immediately before application may be, for example, 1% by mass to 20% by mass, 2% by mass to 12% by mass, 2% by mass to 10% by mass, or 2% by mass to 8% by mass, based on the total mass of the adhesive layer. In addition, the DMSO concentration in the patch after 24 hours of application is preferably 0.1% by mass to 4% by mass, more preferably 0.1% by mass to 1.5% by mass. The support layer is preferably one that can achieve such a reduction in DMSO concentration. More specifically, when the DMSO concentration in the patch immediately before application is 2% by mass to 8% by mass, the support layer is preferably one that provides a reduction rate of DMSO concentration of 0.08% by mass / hour to 0.16% by mass / hour (i.e., a reduction of 1.92% by mass to 3.84% by mass per 24 hours). From another perspective, when the DMSO concentration in the patch immediately before application is 2% by mass to 8% by mass, it is preferable that the support layer has a half-life of DMSO concentration of 5 hours to 24 hours. If the support layer satisfies such conditions, sufficient adhesion tends to be maintained even after 24 hours of application. The rate of decrease in the DMSO concentration and the half-life of the above-mentioned patch are calculated by placing the patch with the support layer facing upward under conditions of 30°C and 65% RH, and measuring the progress of the DMSO concentration of the patch by gas chromatography (GC).
[0029] The patch can be produced, for example, by the following method, but is not limited thereto, and any known method can be used. First, the components constituting the adhesive layer are mixed in a predetermined ratio to obtain a uniform solution. Next, the solution is applied to a peelable film (release film, release liner) in a predetermined thickness to form an adhesive layer. Next, the support layer is pressed onto the adhesive layer so that the adhesive layer is sandwiched between the release liner and the support layer. Finally, the patch can be obtained by cutting into a desired shape. In this case, the release liner is removed when the patch is applied. EXAMPLES
[0030] (Preparation of Patches) In the following examples, unless otherwise stated, the patches were prepared as follows. 1) The components of the adhesive layer were mixed and applied onto a release film (a release-treated PET film). This was then dried to remove the DMSO to a specified amount, leaving an adhesive layer (100 g / m) with a thickness of 100 μm. 2 ) was formed. 2) A support layer was laminated on the adhesive layer to obtain a patch, which was then cut to an appropriate size.
[0031] (Measurement of moisture permeability of support layer) In the following examples, the moisture permeability of the support layer used was measured under the measurement conditions of 40° C. and 90% RH in accordance with JIS Z0208.
[0032] (Evaluation of adhesiveness of patches) In the following examples, unless otherwise specified, the adhesiveness of the patch was evaluated by the following 180° peel test. 1) A 1cm x 5cm test piece was prepared from the patch and stored under specified conditions for the specified time. 2) The release film was removed from the test piece, and the test piece was attached to a stainless steel plate. 3) Using an Instron tensile testing machine, the test piece was peeled off from the stainless steel plate in a direction of 180° at a speed of 30 cm / min, and the peel force (gF / cm) was measured. 4) The average peel strength (gF / cm) was calculated from the integral of the peel strength in the section showing steady peeling. A high peel strength indicates excellent adhesion.
[0033] (Evaluation of patch adhesion) In the following examples, the adhesion of the patch to the skin was evaluated by the following method. The patch was applied to the skin of the subject. After 24 hours, the degree of adhesion of the patch was visually observed. If 90% or more of the patch area was adhered to the skin, it was rated as "A", otherwise it was rated as "B".
[0034] (Test Example 1) A patch (placebo patch) with the composition shown in Table 1 was prepared. In the table, "PET film," "PET film / PET nonwoven fabric," "PU film / PU nonwoven fabric," and "PET knitted fabric" respectively refer to a film made of PET, a laminate of a film made of PET and a nonwoven fabric made of PET fibers, a laminate of a film made of PU and a nonwoven fabric made of PU fibers, and a knitted fabric made of PET. The rubber-based adhesive in Table 1 is a mixture of SIS block copolymer and PIB, containing SIS block copolymer and PIB in a mass ratio of 19:7. The "PET knitted fabric" is a PET knitted fabric having a moisture permeability of 5667 g / m 2 The patch was stored in an incubator at 30°C and 65% RH with the support layer facing upwards and the release film facing downwards. After 24 hours, DMSO was extracted from the patch and quantified by GC. This storage condition mimicked the environment when the patch was applied to the skin for 24 hours.
[0035] The results are shown in Table 1, Figure 1, and Figure 2. The moisture permeability of the support layer was 400 g / m 2 The patches of Reference Examples 3 and 4, which last for 24 hours or more, have a moisture permeability of 400 g / m 2-The DMSO concentration after 24 hours of storage was significantly reduced compared to the patches of Reference Examples 1 and 2, which were stored for less than 24 hours. A relationship was observed between the patch having a highly moisture-permeable backing layer, in which the rate of decrease in the DMSO concentration in the adhesive layer was high (Figure 1), and the half-life of the DMSO concentration was short (Figure 2).
[0036] The adhesiveness of the patch stored under the same conditions for 24 hours was also evaluated. The results are shown in Table 1. 2 The patches of Reference Examples 3 and 4, which last for 24 hours or more, have a moisture permeability of 400 g / m 2 Compared to the patches of Reference Examples 1 and 2, which were left in place for less than 24 hours, the adhesiveness (peeling strength) after 24 hours of storage was good.
[0037] Furthermore, the adhesiveness after 24 hours of the patch having the composition shown in Table 1 was evaluated. The results are shown in Table 1. 2 The patches of Reference Examples 3 and 4, which were applied for 24 hours or more, had good adhesion after application for 24 hours.
[0038] [Table 1]
[0039] (Test Example 2) Patches were prepared with the composition shown in Table 2. The rubber-based adhesive in Table 2 is a mixture of SIS block copolymer and PIB, containing the SIS block copolymer and PIB in a mass ratio of 19:7. The adhesiveness of the patches of Examples 2 and 7 to 9 was evaluated by the probe tack value measured under the following conditions in accordance with the probe tack test method of ASTM D2979. A high probe tack value means excellent adhesiveness. Testing machine: Tacking testing machine (Rhesca) Probe tip material: Stainless steel Adhesive surface diameter: 5mm Pulling speed: 2mm / sec Adhesive load: 200gF / cm 2 Adhesion time: 1 second
[0040] Furthermore, each of the patches of Examples 1 to 15 and Comparative Examples 1 to 3 was applied to the lower back of a healthy adult male, and the adhesion was evaluated after 24 hours. The results are shown in Table 2. 2 The patches of Examples 1 to 15, which were applied for 24 hours or more, had good adhesion after application for 24 hours.
[0041] Furthermore, the patch of Example 2 was placed in an incubator at 30°C and 65% RH with the support layer facing upward and stored. After 24 hours, the DMSO concentration (mass%) in the adhesive layer was quantified by GC to examine the transition of the DMSO concentration. The DMSO concentration after 24 hours was 1.2 mass% relative to the total mass of the adhesive layer, which is 33% relative to the initial (before storage) DMSO concentration of 100%. The rate of decrease in the DMSO concentration calculated from the change in DMSO concentration was 0.1 mass% / hour, and the half-life was 15 hours.
[0042] [Table 2]
[0043] (Test Example 3) A patch having the composition shown in Table 3 was prepared. For the patch having the composition shown in Table 3, the probe tack value was measured in the same manner as in Test Example 2 to evaluate the adhesiveness. The rubber-based adhesive in Table 3 is a mixture of SIS block copolymer and PIB, containing SIS block copolymer and PIB in a mass ratio of 19:7. "Rubber / polyester cloth" in Table 3 means polyester cloth coated with a rubber composition. The PU film in the patch of Example 16 (moisture permeability 786 g / m 2 24 hours), and the PU film in the patch of Examples 17, 19, and 20 (moisture permeability 8408 g / m 2 -24 hours) are 3M's "3M CoTran 9701 Backing" and "3M CoTran 9700", respectively.
[0044] The adhesive properties of the patches of Examples 16 to 19 and Comparative Examples 4 and 5 were evaluated after 24 hours. The results are shown in Table 3. The patches of these Examples and Comparative Examples were stored in an incubator at 30°C and 65% RH, with the backing layer facing upwards. After 24 hours, the DMSO concentration (mass%) in the adhesive layer was quantified by GC to examine the change in DMSO concentration over time. The results are shown in Table 3. When the moisture permeability of the backing layer was 400 g / m 2 The patches of Examples 16 to 19, which were applied for 24 hours or more, had good adhesion after application for 24 hours.
[0045] [Table 3]
Claims
1. A support layer and a pressure-sensitive adhesive layer laminated on the support layer, The moisture permeability of the support layer is 400 g / m 2 - 24 hours or more, A patch, the adhesive layer comprising a drug, dimethyl sulfoxide, and an adhesive, the concentration of dimethyl sulfoxide immediately before application is 2% by mass to 10.9% by mass relative to the total mass of the adhesive layer; A patch, wherein the support layer is such that the half-life of the concentration of dimethyl sulfoxide is 4 hours to 24 hours.
2. 2. The patch according to claim 1, wherein the pressure-sensitive adhesive layer has a probe tack value of 30 gF or more.
3. 3. The patch according to claim 1, wherein the 50% modulus of the support layer in the longitudinal and transverse directions is 1 N / 50 mm to 12 N / 50 mm.
4. The patch according to any one of claims 1 to 3, wherein the support layer is a laminate of a film made of polyurethane and a nonwoven fabric made of polyurethane fibers, a knitted fabric made of polyethylene terephthalate, a film made of polyurethane, a nonwoven fabric made of polyurethane fibers, or a polyester cloth coated with a rubber composition.
5. The moisture permeability of the support layer is 750 g / m 2 The patch according to any one of claims 1 to 4, which is effective for 24 hours or more.
6. The moisture permeability of the support layer is 2000 g / m 2 The patch according to any one of claims 1 to 4, which is effective for 24 hours or more.
7. The patch according to any one of claims 1 to 6, wherein the adhesive layer comprises at least one adhesive selected from a rubber-based adhesive, an acrylic-based adhesive, and a silicone-based adhesive.
8. The patch according to any one of claims 1 to 6, wherein the adhesive layer comprises a styrene-isoprene-styrene block copolymer.
9. The patch according to any one of claims 1 to 8, wherein the drug is one or more drugs selected from the group consisting of ketoprofen, diclofenac sodium, and indomethacin.
10. The patch according to any one of claims 1 to 8, wherein the drug is diclofenac sodium.
11. The patch according to claim 9 or 10, wherein the adhesive layer comprises an organic acid.
Citation Information
Patent Citations
Patches
JP7583889B2
Patch material
WO2010137699A1
Adhesive patch and use thereof
WO2011136330A1
Skin patch
WO2013191128A1